Genetic Analysis of Photoperiod/Thermosensitive Male Sterility in Rice under US Environments. Issue 4 (25th May 2017) - De Guzman, Christian; Esguerra, Manuel; Linscombe, Steve; Berger, Greg; Sha, Xueyan; Oard, James
Abstract : Two‐line hybrid rice ( Oryza sativa L.) breeding in the United States and China uses photoperiod/thermosensitive genetic male sterility (PTGMS) to produce lines with fertile or sterile pollen, depending on temperature and/or daylength. Although studied in China for >30 yr, genetic analysis of PTGMS in US environments is lacking. We therefore conducted genetic studies of male sterility over 3 yr in five F2 and BC1 F2 populations derived from PTGMS line 2008S in Louisiana and Arkansas. Chi‐squared analyses in all populations indicated that sterility was controlled at both locations by two or three recessive genes. Inheritance and expression of PTGMS was found to be influenced by the particular combination of population and year (environment). Sequence comparisons of two regions in PTGMS loci LOC_Os07g12130 and LOC_Os12g36030 from six fertile and sterile lines revealed a diagnostic single‐nucleotide polymorphism (SNP) at each locus. Two‐way ANOVA in two F2 populations inferred that interaction of the two SNP‐containing regions contributed up to 65% variation for sterility in one Louisiana environment. Selective genotyping of the 2008S/CL131 F2 population detected new quantitative trait loci with R 2 values ranging from 5 to 27% using single‐marker and composite‐interval mapping. Results from this study indicate that 2008S can be used as parental material for development of two‐line hybrids in Louisiana and Arkansas, but extensive testing of populations across years and locations will be required.